Impact of persistence to secondary preventive medication on prognosis for patients with myocardial infarction with and without obstructive coronary arteries - Anna M. Nordenskjöld; Lars Lindhagen; Björn Wettermark; Bertil Lindahl (PLoS ONE, 2025)
Background Poor adherence to secondary preventive medication after myocardial infarction (MI) negatively affects long-term prognosis, but knowledge is lacking regarding the impact of poor adherence on prognosis for patients with myocardial infarction with non-obstructive coronary arteries (MINOCA). We therefore investigated the effect of persistence to secondary preventive medication on prognosis in patients with MINOCA compared with patients with myocardial infarction with obstructive coronary arteries (MI-CAD). Methods In this nationwide observational study of 116,143 patients with MI recorded in the SWEDEHEART registry between 2006─2017, MINOCA were identified in 9,124 patients and MI-CAD in 107,019 patients. Persistence to treatment with aspirin, statins, beta blockers and angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin-receptor blockers (ARBs) was investigated for 5 years post discharge and patients were followed for a composite endpoint of major adverse cardiovascular events (MACE), including all-cause death, MI, ischemic stroke and heart failure. Results Persistent use of secondary preventive medications was associated with a decrease in the risk of MACE during follow-up in both MINOCA and MI-CAD patients; aspirin HR 0.70 (CI 0.60–0.82) vs. HR 0.60 (CI 0.57–0.64), statins HR 0.80 (CI 0.68–0.95) vs. HR 0.66 (CI 0.63–0.69), beta blockers HR 0.77 (CI 0.65–0.92) vs. HR 0.76 (CI 0.73–0.80) and ACEIs/ARBs HR 0.62 (CI 0.50–0.77) vs. 0.67 (CI 0.63–0.71). Conclusion Persistence to secondary preventive medications after MI is associated with a reduction in the risk for MACE in both patients with MINOCA and MI-CAD. Continuous efforts to improve adherence to evidence-based medications in general to all patients with MI should be a priority.